Wet compounding with pyrolytic carbon black from waste tyre for manufacture of new tyre – A mini review. Issue 12 (December 2021) - Xu, Junqing; Yu, Jiaxue; He, Wenzhi; Huang, Juwen; Xu, Junshi; Li, Guangming
Pyrolysis offers a more focused alternative to waste tyres treatment. Pyrolytic carbon black (CBp), the main product of waste tyre pyrolysis, and its modified species can be applied to tyre manufacturing realizing its high-value utilization. Modified pyrolytic carbon black/natural rubber composites prepared by a wet compounding (WC) and latex mixing process have become an innovative technology route for waste tyre remanufacturing. The main properties and applications of CBp reported in recent years are reviewed, and the main difficulties affecting its participation in tyre recycling are pointed out. The research progress of using WC technology to replace dry mixing manufacturing of new tyres is summarized. Through literature data and comparative studies, this paper points out that the characteristic of high ash content can be well utilized if CBp is applied to tyre manufacturing. This mini-review proposes a new method for high-value utilization of CBp. The composite mixing of CBp and carbon nano-materials under wet conditions is conducive to the realization of their good dispersion in the rubber matrix. This provides a new idea for customer resource integration and connection of industry development between the tyre production industry and waste tyre disposal management.